Silver-loaded mesoporous silica nanoparticles enhanced the mechanical and antimicrobial properties of 3D printed denture base resin. (October 2022) - Aati, Sultan; Aneja, Seerat; Kassar, Michael; Leung, Ryan; Nguyen, Anh; Tran, Susan; Shrestha, Barsha; Fawzy, Amr
Abstract: The aim of this study is to develop a novel 3D printed denture base resin material modified with mesoporous silica nanocarrier loaded with silver (Ag/MSN) to enhance mechanical and antimicrobial properties. Acrylate resin-based was incorporated with various proportion of Ag/MSN (0.0–2.0 wt%). Specimens with different geometry were printed and characterized accordingly for the effect of modification on properties such as: mechanical and physical properties, chemical composition and degree of conversion, as well as biological response in term of biocompatibility and antimicrobial against oral fibroblast and candida biofilm ( C. albicans ), respectively. The consecutive addition of Ag/MSN improved significantly surface hardness and crack propagation resistance, while flexural strength remained similar to control; however, a negligible decrease was observed with higher concentrations ≥1 wt%. No significant difference was noticed with water sorption, while water solubility had a remarkable trend of reduction associated with filler content. The surface roughness significantly increased when concentration of Ag/MSN was ≥1.0 wt%. A significant reduction in C. albicans biofilm mass, as the inhibition proficiency was correlated with the proportion of the filler. With respect to the amount of Ag/MSN, the modification was compatible toward fibroblast cells. The sequential addition of Ag/MSN enhanced significantly the mechanical and antimicrobial properties of the 3D printed resin-based material without affecting adversely compatibility. The acrylic resin denture base material has susceptibility of microbial adhesion which limits its application. Silver loaded MSN showed a significant performance to enhance antimicrobial activity against C. albicans which is the main cause of denture stomatitis. The proposed invention is a promise technique for clinical application to provide an advanced prosthesis fabrication and serve as long-term drug delivery. Graphical abstract: Image 1 Highlights: 3D printed material with advanced properties were attained using Ag/MSN. Drug delivery nanoparticles showed a homogenize distribution across 3D printed matrix. Ag/MSNs have contributed remarkably to enhance material's toughness, surface hardness and nanoindentation. Modified composition reveled outstanding antimicrobial properties associated with Ag/MSNs concentration.